Optimization of Ce3+ concentration and Y4MgSi3O13 phase in Mg2+‐Si4+ Co‐doped Ce: YAG ceramic phosphors. Issue 11 (10th August 2020) - Tian, Yanna; Tang, Yanru; Yi, Xuezhuan; Chen, Jie; Sun, Shiyu; Zhao, Di; Lin, Hui; Zhou, Shengming
Abstract: As a promising replacement for nitride red phosphors, Ce: Y3 (Mg1.8 Al1.4 Si1.8 )O12 (Ce: YMASG) ceramic phosphors have attracted significant attention recently for their advantages in inorganic encapsulation and massive red‐shifting of Ce 3+ emission. In this work, Ce: YMASG with different doping concentrations of Ce 3+ and Al2 O3, was fabricated by vacuum sintering to investigate its effects on the elimination of the impurity phase and the enhancement of the luminescent properties of white light‐emitting diodes (w‐LEDs). It was discovered that the emission wavelength redshifts from 592 to 606 nm as the Ce 3+ concentration increases, while at 450 K, the emission intensity deteriorates from 0.47 to 0.36 of its initial value. The Rietveld analysis revealed the presence of an impurity phase of Y4 MgSi3 O13 with a concentration of 17.021 wt% in Ce: YMASG. With the introduction of Al2 O3, the impurity phase was eliminated from the matrix completely, the emission peak shifted to a shorter wavelength, and the thermal stability was greatly improved. When the correlated color temperature was controlled at around 3000 K in the packaged w‐LEDs, the commission international de l'éclairage (CIE) chromaticity coordinates shifted toward the bottom left corner of the diagram with increasing concentration of Ce 3+ . Conversely, the luminous efficiency (LE) increased from 36 lm/W to 58.6 lm/W as the concentration of Al2 O3 increased from 0 to 10 wt%, which demonstrated the application prospect of the fabricated phosphor in warm w‐LEDs.